2014
DOI: 10.1128/mbio.01446-14
|View full text |Cite
|
Sign up to set email alerts
|

Serine/Threonine Protein Phosphatase-Mediated Control of the Peptidoglycan Cross-Linking l , d - Transpeptidase Pathway in Enterococcus faecium

Abstract: The last step of peptidoglycan polymerization involves two families of unrelated transpeptidases that are the essential targets of β-lactam antibiotics. d,d-transpeptidases of the penicillin-binding protein (PBP) family are active-site serine enzymes that use pentapeptide precursors and are the main or exclusive cross-linking enzymes in nearly all bacteria. However, peptidoglycan cross-linking is performed mainly by active-site cysteine l,d-transpeptidases that use tetrapeptides in Mycobacterium tuberculosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Recombinant StpA containing a C-terminal 6-histidine tag was produced in Escherichia coli BL21(DE3) and purified by nickel affinity and size exclusion chromatography methods, as previously described (11). Hydrolysis of para-nitrophenyl-phosphate (Sigma) by StpA was determined at 37°C in 50 mM Tris-HCl (pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recombinant StpA containing a C-terminal 6-histidine tag was produced in Escherichia coli BL21(DE3) and purified by nickel affinity and size exclusion chromatography methods, as previously described (11). Hydrolysis of para-nitrophenyl-phosphate (Sigma) by StpA was determined at 37°C in 50 mM Tris-HCl (pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
“…A second mutation was detected in the protein phosphatase gene stpA of mutant M1 located upstream from the Ser/Thr protein kinase gene stk (11). The stpA mutation of M1 impairs the phosphatase activity of StpA, leading to hyperphosphorylation of Stk and several uniden- tified proteins (11). Genetic analyses showed that impaired phosphatase activities of DdcS and StpA are both required and sufficient for high-level ampicillin resistance (11 (12).…”
Section: ¡D-iasx-l-lysmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutation in the PBP gene, however, translates into a slightly different but functional protein which prevents the binding of β-lactam antibiotics such as penicillin [18][19][20]. Examples of microbes harboring this ability are drug-resistant strains of Clostridium difficile, Enterococcus faecium and Streptococcus pneumoniae [21][22]. In addition, microbial resistance towards ciprofloxacin, which interferes with cellular division through interaction between the DNA gyrase and topoisomerase, is also categorized under this mechanism [23][24].…”
Section: Modification Of Antibiotic's Target Sitementioning
confidence: 99%